Joint Effects of Body Mass Index and Waist Circumference on the Incidence of Hypertension in a Community-Based Chinese Population - Mohetaboer Momin; Fangfang Fan; Jianping Li; Jia Jia; Long Zhang; Yan Zhang; Yong Huo (Obesity Facts, 2020)
Objective: We aimed to investigate the relationships of body mass index (BMI), waist circumference (WC), and obesity defined using a combination of both indexes, with the incidence of hypertension in a Chinese community-based population. Methods: A total of 1,927 Chinese participants (57.2 ± 8.9 years old) with normal blood pressure at baseline were recruited from the Shijingshan community in Beijing. Incident hypertension was defined as blood pressure ≥140/90 mm Hg, self-reported hypertension, or the use of any antihypertensive medication at the follow-up visit. Results: During 2.3 years of follow-up, 19.1% (n = 97) of the men and 13.6% (n = 158) of the women developed incident hypertension. The adjusted odds ratios (ORs) (95% confidence intervals [CIs]) for obesity (BMI ≥30) were 3.49 (1.59–7.66) and 2.60 (1.48–4.55) for men and women, respectively. A 1-point increase in BMI was associated with 8% (OR = 1.08, 95% CI: 1.00–1.17) and 10% (OR = 1.10, 95% CI: 1.05–1.16) increases in the incidence of hypertension in men and women, respectively. Abdominal obesity (WC ≥90 cm in men and ≥85 cm in women) was positively associated with incident hypertension in both men (adjusted OR = 1.79, 95% CI: 1.10–2.91) and women (adjusted OR = 1.61, 95% CI: 1.09–2.40). A 1-cm increase in WC was associated with 4% (adjusted OR = 1.04, 95% CI: 1.01–1.07) and 4% (adjusted OR = 1.04, 95% CI: 1.02–1.07) increases in the incidence of hypertension in men and women, respectively. The combination of abnormal BMI and WC has the highest risk for hypertension in both men (adjusted OR = 3.10, 95% CI: 1.48–6.50) and women (adjusted OR = 2.51, 95% CI: 1.43–4.40). Conclusions: This study shows that BMI, WC, and an index that combined the two are independently associated with incident hypertension in a Chinese community-based population.